Applications of the light laser with spatial incoherence and bionic optimization to the optical wireless communications: The light laser with spatial incoherence and bionic optimization in optical wireless communications (Revista de Investigaciones Universidad del Quindío, 2014)
The bioelectronics takes of the biology the optimized elements for to do a copy and to build technological mechanisms with functions based in that of body lives components. Telecommunications and biology present an analogy between the optical receivers and insects eyes, which forms are adequate to receipt signal since a transmitter, and these are been leaded to perfection by the nature during millions of years in the environment adaptation. The sizes and the forms depend of the direction of the waves and of the radiation pattern of these biotransmitters and bioreceivers (omatidies of insects eyes), which is similar as the optical communications emitters and photodetectors. The growth of the telecommunication services makes necessary the optimization of the bandwidth of the transmission channels. Although the optic transmission is considered like the ideal as for the attenuation and distortion characteristics that make that it possesses the better relation bandwidth - longitude, the demand of more transmission capacity forces to take advantage of them efficiently. High costs generated when deploying Optic Fiber Networks at the transport level, together with other factors that avoid PONs arriving to the home and/or office, have impulsed the design and implementation of partially optical networks (FITL), including an alternative that uses infrared light. This work explores the basis of these news access networks, and it is presented an optical communication transmission/reception system with optic channel of free space where has been modulated the transmitter laser through a set of spherical lens and optical fibers that expand the beam of light to different points of an indoor enclosure producing multiple punctual images located in positions that permit to determine and to optimize the bandwidth of the system. The computational simulation results are showed and are compared with those experimentally measured, indicating that this is an original method for to design emitters and receivers of high performance for optical communications.
Keywords: Bioelectronics; photodetectors; photoemitters; omatidio; broadband; Free Space Optics (FSO); optoelectronics; spatial coherence; wireless optic communications; spatial modulation; laser